Fast Mapping of Novel Word Forms Traced Neurophysiologically - Shtyrov, Yury (Frontiers in Psychology, 2011)
Human capacity to quickly learn new words, critical for our ability to communicate using language, is well-known from behavioural studies and observations, but its neural underpinnings remain unclear. In this study, we have used event-related potentials to record brain activity to novel spoken word forms as they are being learnt by the human nervous system through passive auditory exposure. We found that the brain response dynamics change dramatically within the short (20 min) exposure session: as the subjects become familiarised with the novel word forms, the early (~100 ms) fronto-central activity they elicit increases in magnitude and becomes similar to that of known real words. At the same time, acoustically similar real words used as control stimuli show a relatively stable response throughout the recording session; these differences between the stimulus groups are confirmed using both factorial and linear regression analyses. Furthermore, acoustically matched novel non-speech stimuli do not demonstrate similar response increase, suggesting neural specificity of this rapid learning phenomenon to linguistic stimuli. Left-lateralised perisylvian cortical networks appear to be underlying such fast mapping of novel word forms unto the brain’s mental lexicon.